KOMPARASI SISTEM TANAM JAJAR LEGOWO DAN KONVENSIONAL PADA PRODUKSI DAN PENDAPATAN USAHA TANI PADI SAWAH DI DESA KUIMASI KECAMATAN FATULEU KABUPATEN KUPANG - Piga, Aprillia E.; Nendissa, Doppy Roy; Bernadina, Lika (Undana Press, 2024)
The Jajar Legowo planting system is a new innovation which in its application aims to increase production and income in lowland rice farming businesses when compared with Conventional planting systems, so this study aims to determine production and income and the magnitude of the difference in productivity and income from lowland rice farming using the Jajar Legowo and Conventional planting systems in Kuimasi Village, Fatuleu District, Kupang Regency. To find out the production and income of rice farming, it is necessary to calculate the farmer's income level using farming income analysis calculations. The results of this study (1) The total production cost of lowland rice farming in Kuimasi Village, Fatuleu District, Kupang Regency using the Jajar Legowo planting system is IDR. 8,420,754.3/Ha, total revenue of Rp. 41,250,000/Ha with an average income of Rp. 32,829,245.7/Ha and the total cost of lowland rice production using a conventional planting system is Rp. 7,258,456.3/Ha, total revenue of Rp. 52,500,000/Ha with an average income of Rp. 45,241,543.7/Ha. (2) The total production costs of lowland rice farming using the Jajar Legowo planting system and the conventional planting system have a difference of Rp. 1,162,289/Ha. The total revenue from rice farming using the Jajar Legowo planting system and the conventional planting system has a difference of Rp. 11,250,000/Ha. The average income using the Jajar Legowo planting system and the conventional planting system has a difference in income of Rp. 12,412,298/Ha in one planting season. Based on these calculations, it can be concluded that the total production costs using the Jajar Legowo planting system are greater than the total production costs using the Conventional planting system, but the total revenue and income using the Conventional planting system is greater than the total revenue and income using the Jajar Legowo planting system.